PENERAPAN KOMBINASI TERAPI AKUPRESURE & PIJAT OKETANI UNTUK MENINGKATKAN PRODUKSI ASI PADA IBU MENYUSUI 0-6 BULAN DI DESA BANTARJAYA TAHUN 2024 - Neneng Julianti (PROFICIO, 2024)
Based on the results of a preliminary study conducted by the author to Bantarjaya Village, Pebayuran District, Bekasi Regency, no one has ever applied a combination of Acupressure Therapy & Oketani Massage when providing obstetric care to postpartum mothers. The purpose of this community service activity is to increase knowledge/understanding of acupressure therapy and oketani massage in increasing breast milk production in breastfeeding mothers 0-6 months. The implementation method is by providing socialization / counseling and followed by demonstrations in conducting acupressure therapy and Oketani Massage. This Community Service activity was carried out in Bantarjaya Village, the Working Area of the Pebayuran Health Center, Bekasi Regency on the Day/date: Saturday & Sunday, 25 & 26 May 2024 at 09.00 to 16.00 WIB with the result that there was an increase in knowledge / understanding of 96.35% in the good category of the use of acupressure therapy & oketani massage. So that the percentage increase in knowledge/understanding is 35.43%. Then the evaluation was carried out on Saturday & Sunday, 01 & 02 June 2024 at 09.00 to 16.00 in Bantarjaya Village, Pebayuran District, Bekasi by implementing acupressure therapy & massage therapy. As a result, there is an increase in breast milk production on average by around 75%. With a characteristic or sign of increased breast milk production is when pumped > 300-500 ml.